Character of cell-free genomic DNA in embryo culture medium and the prospect of its clinical application in preimplantation genetic testing. Issue 1 (March 2022) - Lei, Cai-Xia; Sun, Xiao-Xi
Abstract : Abstract: There is increasing evidence that cell-free DNA (cfDNA) in spent culture media (SCM) can be amplified for genetic testing. Therefore, this paper reviews the characteristics of cfDNA, including its fragment size, amount, origin, as well as some factors affecting the success rate of its amplification, together to provide researchers with a more comprehensive perspective on embryonic cfDNA. The origin of cfDNA in SCM is complicated and poses challenges to the interpretation of genetic test results. Advanced molecular techniques should distinguish between embryonic and contaminated DNA to maximize the success rate of amplification and analysis. Recent data showed that the type of culture medium, assisted hatching or not, the type of amplification kit, and fresh or thawed embryos were not related to the success rate of amplification, but the length of culture time might affect the success rate. The longer culture time, the more cfDNA is available in the SCM. Then we focused on the concordance between trophectoderm (TE), inner cell mass, whole embryo, and embryonic cfDNA. Despite successful amplification, the concordance between TE and embryonic cfDNA was low. In summary, non-invasive genetic testing using SCM could represent a major advance in future single embryo selection, however, contamination and timing for media collection are key factors affecting the results, and current noninvasive cfDNA testing should not be directly applied to clinical practice. Further research is needed to improve the methods used for testing techniques and genetic analysis to achieve greater accuracy and trace its origins before it can be used in the clinics.